E7 proteins from oncogenic human papillomavirus types transactivate p73: role in cervical intraepithelial neoplasia. - Brooks,LA; Sullivan,A; O'Nions,J; Bell,A; Dunne,B; Tidy,JA; Evans,DJ; Osin,P; Vousden,KH; Gusterson,B; Farrell,PJ; Storey,A; et al. (Br J Cancer, 2002)
In common with other E2F1 responsive genes such as p14(ARF) and B-myb, the promoter of p73 is shown to be positively regulated in cell lines and primary human keratinocytes by E7 proteins from oncogenic human papillomavirus (HPV) types 16, 18, 31 and 33, but not HPV 6. Mutational analysis revealed that transactivation of the p73 promoter by HPV 16E7 requires association with pRb. Expression of p73 in normal cervical epithelium is confined to the basal and supra-basal layers. In contrast, expression in neoplastic lesions is detected throughout the epithelium and increases with grade of neoplasia, being maximal in squamous cell cancers (SCC). Deregulation of expression of the N-terminal splice variant p73Delta2 was observed in a significant proportion of cancers, but not in normal epithelium. The frequent over-expression of p73Delta2, which has recognized transdominant properties, in malignant and pre-malignant lesions suggests a role in the oncogenic process in cervical epithelium.